Diagnostic Ability and Capacity of Optical Coherence Tomography-Angiography to Detect Retinal and Vascular Changes in Patients with Fibromyalgia - Elena Garcia-Martin; Alvaro Tello; Elisa Vilades; Javier Perez-Velilla; Beatriz Cordon; Diego Fernandez-Velasco; Javier Garcia-Campayo; Marta Puebla-Guedea; Maria Satue (Journal of Ophthalmology)
Background. To evaluate the neuroretina and retinal vasculature of fibromyalgia (FM) patients and calculate a linear discriminant function (LDF) to improve retinal parameters’ contribution to FM diagnosis. Methods. Fifty FM patients and 232 healthy controls underwent retinal evaluation using swept-source optical coherence tomography (SS-OCT) angiography (Triton plus; Topcon) and spectral domain OCT (SD-OCT) (Spectralis; Heidelberg). The macular (m) and peripapillary (p) retinal nerve fibre layer (RNFL) and ganglion cell layer (GCL) were assessed, as was the macular vascular density. A logistic regression analysis was performed, and an LDF was calculated to evaluate OCT’s contribution to FM diagnosis. Results. With Triton OCT, the patients presented pRNFL thinning in the temporal sector (p=0.006). Spectralis OCT measurements showed decreased pRNFL in patients in the following sectors: superonasal, p=0.001; nasal, p=0.001; inferonasal, p=0.006; temporal, p=0.001; and inferotemporal, p=0.001. No significant differences were observed in the macular vascular plexus between patients and controls. However, vascular density in the superior sector showed a strong inverse correlation with disease duration (r = −0.978, p=0.022). The LDF calculated for Spectralis OCT yielded an area under the ROC curve of 0.968. Conclusions. FM patients present RNFL thinning observable using SS- and SD-OCT. However, these patients show similar vascular density in the macular area to healthy controls. The LDF that combines several RNFL parameters obtained using Spectralis OCT gives this device a powerful ability to differentiate between healthy individuals and individuals with FM.